Faktor-Faktor Risiko Terjadinya Stunting Anak Usia di Bawah 5 Tahun - Rizki Kurniadi; Sigit Mulyono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Stunting is one of the nutritional problems that can significantly inhibit human development. Controlling the factors that cause stunting can reduce the incidence of stunting. The purpose of this study is to identify the risk factors of stunting in children under 5 years old (toddlers). The method used was a systematic literature review which was analyzed using descriptive approach. The data obtained from online database such as PubMed; CINAHL; Sciencedirect; Medline; Google Scholar. The results of the study identified the risk factors of stunting were maternal factors including maternal nutrition before pregnancy, during pregnancy, and breastfeeding; maternal stature; age